„Nowa świadomość Kościoła”. Sobór Watykański II oraz idea Kościoła otwartego w tekstach głównych przedstawicieli środowiska „Tygodnika Powszechnego” i „Znaku” - GŁĄB, Anna (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
The article focuses on the presentation of the most important events of the Second Vatican Council through the prism of their reception and interpretation in the articles published in the journals Tygodnik Powszechny and Znak by their eminent commentators and columnists (Jerzy Turowicz, Halina Bortnowska, Anna Morawska, Fr. Andrzej Bardecki, Stefana Wilkanowicz, and Fr. Andrzej Zuberbier, among others). A presentation of the hopes and expectations concerning the Council, expressed in the articles in question, is followed by a description of the Conciliar debates with reference to the category of the «Church of Nazareth,» embracing the new role of the laity in the community of the Church. In this vein, also the reception of Scheme XIII (which was promulgated as the Pastoral Constitution on the Church in the Modern World Gaudium et Spes) is analyzed. The concluding section of the article comprises a study of the new understanding of the Church and the world put forward by the Council, as well as a discussion of the causes and ways to overcome the post-Conciliar crisis in the Church. Translated by Dorota Chabrajska